MEANS OF ANALYZING PARAMETERS OF SPEECH SIGNAL TRANSMISSION AND REPRODUCTION - Azarov, Olexiy; Azarova, Larysa; Krak, Iurii; Krupelnitskyi, Leonid; Azarova, Anzhelika; Azarova, Veronika (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The article explores the design and use of the analyzer developed by the authors for investigating the quality of compression, recording, transmission, and reproduction of speech signals in audio communication channels. The peculiarities of the construction of measurement channels of a self-adjusting system are studied. Parameters for assessing the quality of channels are selected, and methods for their calculation are determined. An example of determining the quality of compression-decompression in satellite channels for transmitting audio speech is provided. A polyharmonic signal, consisting of the sum of many harmonic components with the same amplitude and phase, is proposed as the input test signal for the compressor. Such a signal approximates real speech and music signals transmitted through the channel. The actual frequency characteristic is determined at the output of the decompressor by analyzing the spectrum, which, for the MPEG Layer3 compression method, significantly depends on the bit rate of compressed data transmission. Another characteristic application of the analyzer is experiments to study the structural organization of connecting possibilities of elements in complex nominations at the phonetic level in the concept of the "golden" ratio. A hypothesis is put forward about the harmony of these words at the acoustic level. It is proved that the harmonious structure of juxtapositions should be considered as the arrangement of components of such nominations by a system of perfect relationships, among which the proportion corresponding to the division of the whole into two parts and called the "golden" ratio plays a fundamental role.